(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Friendship is not a positive social relationship full of moral values .Rather ,it is an essential existential component that has to do with the human soul on all levels starting from the significance of a friend in understanding the other, who represents the major characters in the handled novels of research .The research aims at representing a social-philosophical compromise of friendship from a comparative perspective dealing with three novels different in time and theme to get the relation which exceeds being an embodiment with which the friend lives with his friend to the self and the other in the major characters which its special world shaped by blending the life experience with the reality portrayed shaped by this relation.In conclusion ,it aims that friendship is a vital active discourse .The most rational part derivate the self of the social weak part , to show his opinion toward self and world.